Amplification of mtDNA control region in opportunistically collected bird samples belonging to nine families of the order Passeriformes. Issue 1 (1st January 2017) - Singh, Ashutosh; Kumar, Ajit; Kumar, Ramani Suresh; Bhatt, Dinesh; Gupta, Sandeep Kumar
Abstract: We describe six sets of primers for amplifying the mitochondrial control region (CR) of various bird species belonging to nine families of the order Passeriformes. These overlapping primers, with both short and long fragments, yielded an approximately 1 kb fragment of the CR. The short length of the amplified product makes the primers suitable for degraded DNA samples. These primers were used on a wide range of bird species for amplifying and sequencing the highly variable portion of the CR. The primers proved to be a valuable tool for studying the population genetics of bird species. The different sets of primers provide the researcher a choice of markers for different sample types and studies.